Polymer Brush‐Based Asymmetric Porous Patch with Excellent Anti‐Bacterial and Anti‐Contamination Properties Enables Infectious Abdominal Wall Defect Repair - Zeping Huang; Weiwen Liang; Binying Peng; Yang Ouyang; Zixin Chen; Mawsoom Mamut; Zhipeng Huang; Hui Wang; Rongkang Huang; Bo Ma; Bingna Zheng; Jian Cai (Advanced Science)
Abstract Well‐integration of multiple bioactive components into a biological patch without damaging its cellular matrix structure is crucial for infectious abdominal wall defect repair but remains challenging. Herein, a novel asymmetric biological composite patch (bPVA/SIS+‐NP) is developed by in situ introducing zwitterionic polyvinyl alcohol molecular brush (bPVA) hydrogel to a cationic small intestinal submucosal decellularized matrix (SIS+) via a self‐induced phase separation based united strategy. Due to its high hydrogen bonding crosslinking and strong mechanical interlocking with SIS+‐NP layer, bPVA layer can maintain stable anti‐contamination and the corresponding anti‐adhesion properties in the contaminated environment. On the basis of preserving an original extracellular matrix skeleton, SIS+‐NP layer can show strong contact anti‐bacterial ability at the acute stage of repair together with the prolonged drug release during the healing stage of repair. Furthermore, the in situ combination of bPVA and SIS+‐NP layers can lead to a high and stable burst pressure tolerance. By comprehensive control of bacteria and their necrotic products, bPVA/SIS+‐NP patch can achieve anti‐infection, anti‐adhesion, and pro‐healing properties in the infectious abdominal wall defect on rats. Therefore, the bPVA/SIS+‐NP patch opens a new avenue for bio‐friendly construction of multifunctional biological patches to address the stringent requirements of infectious abdominal wall defect repair.